1987
DOI: 10.1111/j.1755-3768.1987.tb07006.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes and lens position 2½ years after intracapsular cataract extraction with implantation of a semiflexible anterior chamber lens

Abstract: Morphological changes and lens position were examined in 51 patients 25 to 38 (mean 30) months after intracapsular cataract extraction (ICCE) with implantation of the semiflexible, 3M, style 70, anterior chamber lens. Morphological changes presumably associated with the ICCE proper were: iris transillumination defects (68.6%), rupture of anterior hyaloid membrane (20%), detachment of posterior vitreous (42.9%) and anterior synecchiae (13.7%). The implant-related morphological changes were caused by iris tuckin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Since this study we have consistently attempted to implant the lenses with both haptics in the capsular bag, which may cause less iris contact (Apple et al 1985). It should be emphasized, that implantation of anterior chamber lenses cause similar progressive reactive changes around the tips of the lens haptics in the chamber angle (Naeser et al 1987).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since this study we have consistently attempted to implant the lenses with both haptics in the capsular bag, which may cause less iris contact (Apple et al 1985). It should be emphasized, that implantation of anterior chamber lenses cause similar progressive reactive changes around the tips of the lens haptics in the chamber angle (Naeser et al 1987).…”
Section: Discussionmentioning
confidence: 95%
“…We conclude that the posterior lens capsule has reached its permanent position by the fourth postoperative month and that the position of a PCL is extremely constant. In contrast, anterior chamber lenses show great variations in post-operative position (Naeser et al 1987). The constant anterior chamber depth implicates an unchanged spherical equivalent refraction beyond the fourth post-operative month.…”
Section: Discussionmentioning
confidence: 97%
“…Ovalling is reported more frequently in cases of semiflexible closed-loop ACLs by Naeser et al (1987) and Story (1987) and in cases with a flexible Simcoe ACL by Laage (1984).…”
Section: Discussionmentioning
confidence: 98%
“…One of our patients developed secondary glaucoma (1.11%). Naeser et al (1987) describes 11.6% secondary glaucomas in ICCE with closed-loop ACL and Kooner et al (1988) found 25.8% secondary glaucomas, of which 11.3% needed long-term medical treatment. Ekdawy (1987) reported glaucoma in 8.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation